Kategoryzacja i oznakowanie więźniów w łagrach na Kołymie w latach 1944-1956 - Marciniak, Wojciech (Acta Universitatis Lodziensis. Folia Historica, 2009)
In the years 1944-1956 the prisoners of Kolyma forced-labour camps (lagry) were divided into three main categories. They were imprisoned in three types of camps, i.e. Corrective Labour Camps (ITL), Hard Labour Camps (katorznyje, KTR) and - since 1948 - Special Camps (OL). The system of Kolyma special camps was named BERLAG (bieregovoj - ‘shore camp’). In the aforementioned kinds of camps prisoners were subject to the respective regimes, with the relatively most lenient in the ITL camps. They had to bear all the hardships of existence in the forced-labour camp, yet a range of possibilities to survive was, in that case, comparatively wide. They could work in the kitchen, the administration of the camp or the utility rooms. Those were the possibilities, which the prisoners of the other camps were deprived of. Nevertheless, more than an inconvenience, even in the ITL was, forced coexistence with the criminal prisoners, who usually harassed and tormented other inmates. The second category was katorga (KTR), prepared, above all, for the prisoners accused of political crimes. They were given identification numbers, which was a change in comparison with the ITL. The convicts were forced to do hardest the most severe labour in mines and could not hold any posts inside the camp. They were treated with rigid strictness by the guards, who put them in fetters on their way to the mines and were permanently in charge. The last group constited of the prisoners of the special camps, which were created all over the Soviet Union after 1948, specially for political prisoners. Eventually, the majority of Polish prisoners, both from the ITŁ and the KTR, were transfered to the Special Camps, with new identification numbers. Relocation meant a change for a worse for many of them. Special Camps constituted a separate and different structure. Specially trained officers of the MWD (Ministerstvo vnutrennich del) were the escorts and guards. Discipline was somewhat similar to that in the KTR camps. The prisoners were put in fetters while going to their work destination and worked in the most difficult conditions. For example the uranium ore mining. The only favourable change was the separation from criminal prisoners, as it put an the terror they had spread in other camps to an end.